Pengembangan media e-modul berbantuan Canva dengan model Problem Based Learning (PBL) untuk meningkatkan kemampuan berpikir kritis siswa Sekolah Dasar - Ai Sutiani; Wikanengsih; D. Fadly Pratama (COLLASE (Creative of Learning Students Elementary Education), 2026)
This research is motivated by the low critical thinking skills of third-grade elementary school students in Science subjects, caused by limited interactive teaching materials and passive learning models. This study aims to develop, test the feasibility of, and analyze the effectiveness of a Canva-assisted e-modul using the Problem-Based Learning (PBL) model in improving students' critical thinking skills. The research employs the Research and Development (R&D) approach using the Borg and Gall model, adapted into 10 developmental stages. Expert validation results indicate that the e-modul is classified as "Highly Feasible," with 94.3% from media experts and 88.5% from material experts, while receiving positive responses from teachers (90.6%) and students (97.8%). Effectiveness testing using the Paired Sample T-Test showed a significance value of 0.000 < 0.05, proving a significant difference in students' critical thinking skills before and after using the media. This is further supported by the N-Gain test results, where the analysis indicator reached a score of 0.81 (effective category), while the evaluation and inference indicators achieved 69.58% and 70.37% (moderately effective category). The study concludes that the development of a PBL-based, Canva-assisted e-modul is effective in stimulating critical thinking skills of elementary school students and is feasible for use as an innovative learning resource.